Some Illustrations of Large Tectonically Driven Climate Changes in Earth History. Issue 12 (25th December 2019) - Ramstein, G.; Godderis, Y.; Donnadieu, Y.; Sepulchre, P.; Fluteau, F.; Zhang, Z.; Zhang, R.; Su, B.; Jiang, D.; Schuster, M.; Besse, J.
Abstract: A century ago, the pioneering book published in 1924 Die Klimate der geologischen Vorzeit explained by plate motion the evolution of vegetation revealed in sedimentary records. Nevertheless, they did not invoke climate changes. In the second part of the 20th century, the intricate relationship between tectonics, long‐term carbon cycle, and climate was depicted by Walker (1981). Since these major steps, climate modeling of the Earth system kept on improving and including more and more components and processes to enable the investigation of deep time periods using general circulation model that can account for atmosphere and ocean dynamics. Here we illustrate long but drastic climate changes clearly related with tectonics, through three different examples: (1) the crucial role of paleogeography (continental distribution) to explain the drawdown of atmospheric carbon dioxide and the huge glaciation associated that occurred during the Neoproterozoic period; (2) the shrinkage of large epicontinental Paratethys that covered a large part of Eastern Europe and Western Asia and its impact on both monsoonal systems (African and Asian) since 40 Ma; and (3) the large impact of mountain range uplifts since Eocene both in Asia (Tibetan Plateau and Himalaya) and in Africa (buildup of the rift), on atmosphere and ocean dynamics. These studies not only allow for testing the ability of Earth system models to capture long‐term changes of Earth climate, but they also pinpoint the pivotal role tectonics played in shaping the long‐term evolution of atmospheric CO2 and monsoon patterns. Plain Language Summary: For the celebration of the 50th anniversary of the publication of the pioneering papers that established the basis of plate tectonic, this paper was solicited to illustrate the close relation between tectonics and climate. Amongst the large spectrum of interactions that depict how tectonics modified the climate at geological time steps, we choose to illustrate two major issues: (1) How the "tryptic" climate/long‐term carbon cycle/tectonics explains the extraordinary glacial episode (717–635 Ma) occurring during Neoproterozoic era? (2) How major tectonic events (i.e., the slow shrinkage of a huge epicontinental sea and the uplift of large mountains ranges in Asia and Africa) drastically changed the climate and shaped the pattern of present‐day monsoons systems. This paper is the result of long‐standing collaboration with many researchers from different countries. Key Points: Relationships between paleogeographic configurations, climate, hydrological cycle and erosionto assess atmospheric CO2 changes Evaluations of climatic impact of uplifts (Tibetan Plateau and African rift) and epicontinental shrinkage (Paratethys) on Cenozoic climates Impacts on Tibetan Plateau uplift on Pacific and Atlantic meridional ocean circulationthrough Cenozoic